(untitled) (Research, Society and Development, 2022)
The development of extruded products with higher nutritional quality and pleasant taste is challenging for the food industry. Therefore, this paper aims to develop an extruded breakfast cereal made of cassava and stevia leaves pretreated with ethanol and provide its chemical and sensorial characterization. We made three breakfast cereal formulas using granulated tapioca flakes and between 0-2% stevia leaves. We determined the moisture, ash, and protein content following the method described by AOAC (2005) and lipid content according to the Goldfish method. To estimate the carbohydrate level, we deducted the sum of all the other values from 100. We evaluated the sensory acceptance through a 9-points hedonic score. Adding stevia leaves to the tapioca breakfast cereal represented a significant increase in chemical composition, increasing the protein level between the formulas. Only ashes and lipids statistically did not differ between the 1%-stevia formula and control. All the formulas were well accepted on the sensory test, and there were no significant differences between the score given to each since all of them achieved from 5.71 to 5.82 for flavor, 5.29 to 6.29 for texture, and 5.53 to 6.29 for global evaluation. The breakfast cereal added of 2% of stevia leaves obtained the lowest percent score at the rejection region and the highest protein content, which is promising in the breakfast cereal production.